Phantom sensations and pain in non-limbs: a systematic literature search - Ramne, Malin; Steinmeier, Lina; Damercheli, Shahrzad (Chalmers University of Technology, 2025)
Phantom pain is most commonly observed and described in the context of limb amputation, then typically referred to as phantom limb pain. However, phantom sensations, including pain, may arise also after the removal or loss of other body parts. This systematic literature search aims to assess the prevalence of phantom sensations and pain in non-limbs. Results were identified for the following body parts: breast, eyes, teeth, rectum, penis, and testes.
Keywords: Clinical Medicine; Klinisk medicin